Markets for technology : the economics of innovation and corporate strategy - Arora, Ashish (MIT Press, 2001)
The past two decades have seen a gradual but noticeable change in the economic organization of innovative activity. Most firms used to integrate research and development with activities such as production, marketing, and distribution. Today firms are forming joint ventures, research and development alliances, licensing deals, and a variety of other outsourcing arrangements with universities, technology-based start-ups, and other established firms. In many industries, a division of innovative labor is emerging, with a substantial increase in the licensing of existing and prospective technologies. In short, technology and knowledge are becoming definable and tradable commodities. Although researchers have made significant advances in understanding the determinants and consequences of innovation, until recently they have paid little attention to how innovation functions as an economic process. This book examines the nature and workings of markets for intermediate technological inputs. It looks first at how industry structure, the nature of knowledge, and intellectual property rights facilitate the development of technology markets. It then examines the impacts of these markets on firm boundaries, the division of labor within the economy, industry structure, and economic growth. Finally, it examines the implications of this framework for public policy and corporate strategy. Combining theoretical perspectives from economics and management with empirical analysis, the book also draws on historical evidence and case studies to flesh out its research results.